2000
DOI: 10.1063/1.481846
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved spectroscopy of a librational fundamental band of hydrogen fluoride tetramer

Abstract: Articles you may be interested inCommunication: Convergence of anharmonic infrared intensities of hydrogen fluoride in traditional and explicitly correlated coupled cluster calculations J. Chem. Phys. 135, 131103 (2011); 10.1063/1.3647566 The HOOH UV spectrum: Importance of the transition dipole moment and torsional motion from semiclassical calculations on an ab initio potential energy surface J. Chem. Phys. 132, 084304 (2010); 10.1063/1.3317438 State-resolved unimolecular dissociation of cis-cis HOONO: Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 80 publications
0
14
0
1
Order By: Relevance
“…The pulsed supersonic expansion and tunable infrared laser systems used to obtain the jet-cooled spectrum in this work have been described in earlier papers, so only those details relevant to this experiment will be discussed [8][9][10][11][12]. Briefly, light from a lead-salt diode laser is mode filtered by a monochromator and then split sequentially by a three-step chopper mirror.…”
Section: Pnnl Measurementsmentioning
confidence: 99%
“…The pulsed supersonic expansion and tunable infrared laser systems used to obtain the jet-cooled spectrum in this work have been described in earlier papers, so only those details relevant to this experiment will be discussed [8][9][10][11][12]. Briefly, light from a lead-salt diode laser is mode filtered by a monochromator and then split sequentially by a three-step chopper mirror.…”
Section: Pnnl Measurementsmentioning
confidence: 99%
“…In the case of the tetramer and pentamer, however, there is still some debate. 23,24 X-ray and neutron diffraction experiments 25 have shown that solid HF tends to form infinite zig-zag chains with very large cooperative effects. Therefore, there must be an inversion of the relative stability of the cyclic and chain isomers as the aggregate grows.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted B value for the tetramer is 0.1358 cm -1 (Maerker et al 1997). Data and analysis of the tetramer parallel band has been recently published (Blake et al 2000). We are presently extending our spectral searches for other intermolecular bands of (HF) n and (DF) n with n = 3-6.…”
Section: High Resolution Infrared Spectroscopy Of Small Molecular Clumentioning
confidence: 82%